Temperature, trophic state, and carrying capacity govern pelagic size spectra in the Atlantic Ocean - Ralf Schwamborn; Tim Dudeck; Claire Carré; Gabriel Bittencourt Farias; María Couret; Javier Díaz-Pérez; Mathilde Dugenne; Gabriela Guerra Araújo Abrantes de Figueiredo; Thierry Frédou; Flávia Lucena-Frédou; Xiomara F.G. Díaz; Dawit Yemane; et al. (Progress in Oceanography, 2026)

Demographic, physiological, psychological, and on-ice performance indicators predict plus/minus status of recreational ice hockey players across a season - Claudio R. Nigg; Andreas Gessner; Carina Nigg; Marco Giurgiu; Rainer Neumann (German Journal of Exercise and Sport Research, 2020)
Little is known about physical, physiological, and psychological performance indicators predicting recreational athletes’ performance. This information may motivate players to become more active and inform coaches where to focus to build confidence, cohesion, and cooperation. This study investigated which performance indicators were related to the plus-minus statistic in German recreational ice hockey players ( n = 20 players; 1 female; mean age = 36.25 ± 12.91 years; height = 178.85 ± 8.64 cm; weight = 81.36 ± 12.89 kg; mean years of ice hockey experience = 5.68 ± 8.93) over a season. Anthropometrics, psychological and on-ice performance data were collected mid-season and plus-minus were recorded after each game. Due to the small sample size, significance interpretations are not meaningful; therefore, Cohen’s guidelines were used for r = 0.2 (small), r = 0.5 (medium) and r = 0.8 (large). Medium size positive correlations of plus/minus were found for push-ups (r = 0.52) and squats (r = 0.37). Small positive correlations were found for shot speed (r = 0.33), competitiveness orientation (r = 0.28), and years on team (r = 0.23). Small negative correlations were found for win orientation (r = −0.30), body mass index (r = −0.28), task cohesion (r = −0.24), and percent body fat (r = −0.20). Some performance and psychological indicators are related to recreational ice hockey players’ plus-minus statistic over a season. Coaches and players of recreational teams should focus on muscular strength and endurance, shooting speed, body composition, and enjoying the challenge of competition while lowering their win orientation.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Phylogeography of the striped field mouse, Apodemus agrarius (Rodentia: Muridae), throughout its distribution range in the Palaearctic region - Alice Latinne; Miguel Navascués; Marina Pavlenko; Irina Kartavtseva; Rainer G. Ulrich; Marie-Laure Tiouchichine; Gilles Catteau; Hela Sakka; Jean-Pierre Quéré; Galina Chelomina; Aleksey Bogdanov; Michal Stanko; et al. (Mammalian Biology, 2020)

Relationships between performance test and match-related physical performance parameters - Stefan Altmann; Maximilian Kuberczyk; Steffen Ringhof; Rainer Neumann; Alexander Woll (German Journal of Exercise and Sport Research, 2018)

Does a 20-week aerobic exercise training programme increase our capabilities to buffer real-life stressors? A randomized, controlled trial using ambulatory assessment - Birte von Haaren; Joerg Ottenbacher; Julia Muenz; Rainer Neumann; Klaus Boes; Ulrich Ebner-Priemer (European Journal of Applied Physiology, 2016)

Rezensionen - Wolf Günther Koch; Werner Stams; Joachim Neumann; Rainer Nitzsche (KN - Journal of Cartography and Geographic Information, 2013)